Environmental liability insurance, green innovation, and mediation effect study - Chen, Yu; Xie, Yuantao (Frontiers in Environmental Science, 2024)
This paper begins by establishing a three-party game model involving three key players: the insurer, the firm, and the government. This model is used to analyze the utility of each party in various scenarios, one of which encourages green innovation within the firm. According to this model, when the insurer rejects insurance coverage and the government maintains a neutral stance on environmental liability insurance, the firm may opt to engage in green innovation. Green innovation fundamentally serves as a mechanism to mitigate environmental pollution risks stemming from the firm’s operational processes. In cases where the insurer declines underwriting, it becomes rational for the firm to enhance its risk management through green innovation, which can be viewed as a mitigating factor in the context of environmental liability insurance. To comprehensively examine the overall impact of environmental liability insurance on the green innovation endeavors of firms, we use a mediation effect model utilizing firm-level data from heavily polluting industries. This paper delves into the intricate relationship between environmental liability insurance and the capacity of heavily polluting firms to engage in green innovation, along with the mediating influence of financing constraints between these two factors. The findings of this analysis suggest that the acquisition of environmental liability insurance enhances the green innovation capabilities of firms operating in heavily polluting industries by alleviating financing constraints, serving as a mediating factor in this regard.